How to revive productivity growth? - Cecilia Jona-Lasinio; Stefano Schiavo; Klaus Weyerstrass (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Providing financial incentives for companies to invest in productivity-enhancing technologies and practices is the key to productivity growth, according to this latest policy report by Cecilia Jona-Lasinio (ISTAT and LUISS Guido Carli), Stefano Schiavo (University of Trento) and Klaus Weyerstrass (Institut für Höhere Studien). Strong investment should also be made into training and workforce skills to exploit the productivity potential of new business models in the digital economy. Competition policy, although not directly related to productivity, is also emerging as an important tool to shape incentives and foster the efficient allocation of resources both across and within sectors and firms. The report analyses the recent trends in labour and total factor productivity in the EU and beyond and identifies factors that influence productivity.
Keywords: 330